Application and Development of ANSYS Parametric Modeling System of RV Reducer - Feng Yubin; Xu Honghai; Liu Xueao; Wang Wentao (Jixie chuandong)
The geometric parameters are defined according to structural features of RV reducer and the secondary development of ANSYS for parametric modeling is finished by using ANSYS parametric design language（ APDL） and user interface design language（ UIDL） based on tooth profile equation of curtate cycloid and involute. The parametric modeling is proved by using the kinematic simulation through Pro / E. The modal analysis of RV- 40 E is finished and the results is coincided with the experimental modal analysis results. By changing the parameter,a study about influence factors of the first order natural frequency is conducted. The influence curve is obtained and it can become the basis of improving dynamic property. The method of parametric modeling of RV reducer could improve the efficiency of finite element analysis by reducing the workload of modeling and avoiding repeated modeling. The application in modal analysis has laid the foundation for the integration of parametric modeling and finite analysis of RV reducer.